Objective rationality and uncertainty averse preferences - Simone Cerreia-Vioglio (Theoretical Economics, 2016)
As in Gilboa, Maccheroni, Marinacci, and Schmeidler GMMS, we consider a decision maker characterized by two binary relations: ^* and ^. The first binary relation is a Bewley preference. It models the rankings for which the decision maker is sure. The second binary relation is an uncertainty averse preference, as defined by Cerreia-Vioglio, Maccheroni, Marinacci, and Montrucchio CMMM. It models the rankings that the decision maker expresses if he has to make a choice. We assume that ^ is a completion of ^*% . We identify axioms under which the set of probabilities and the utility index representing ^* are the same as those representing ^. In this way, we show that Bewley preferences and uncertainty averse preferences, two different approaches in modelling decision making under Knightian uncertainty, are complementary. As a by-product, we extend the main result of Gilboa, Maccheroni, Marinacci, and Schmeidler GMMS, who restrict their attention to maxmin expected utility completions.
Keywords: D81; 330; Ambiguity; Bewley preferences; uncertainty averse preferences; preferences completion